The effect of gallium substitution on the structure and electrochemical performance of LiNiO2 in lithium-ion batteries. Issue 4 (8th June 2020) - Kitsche, David; Schweidler, Simon; Mazilkin, Andrey; Geßwein, Holger; Fauth, François; Suard, Emmanuelle; Hartmann, Pascal; Brezesinski, Torsten; Janek, Jürgen; Bianchini, Matteo
Abstract : Ga-doped LiNiO2 is reinvestigated. Ga is suggested to occupy the Li site. Detailed structural and electrochemical characterization is provided. Abstract : Elemental substitution in lithium nickel oxide (LiNiO2, LNO) is among the most common strategies employed in search of a commercially viable cathode active material (CAM) with the highest possible energy density at reasonable cost (as offered by Ni-rich CAMs). Here, we revisit Ga substitution of Ni in LNO, for which there is a lack of systematic studies, despite promising electrochemical performances reported in the literature. We demonstrate successful synthesis by wet-mixing, pre-annealing and solid-state reaction of the precursors, as shown by electron microscopy and synchrotron-based X-ray diffraction (XRD). The site occupation of Ga ions in the Li interlayer is suggested (corresponding to Li1− y Ga y NiO2 ). Electrochemical testing of the as-prepared CAMs reveals a modified voltage-composition curve upon Li (de)intercalation and improved capacity retention, with the largest specific capacity after 110 cycles obtained for 2.2 mol% Ga content. Operando XRD shows significant differences between structural details of the H2–H3 transition during charge and discharge as well as reduced volume contraction. Although the stabilizing effect of Ga on the LNO structure is clearly evident in our study, degradation upon electrochemical cycling still occurs as shown by the formation of surface rock salt-type layers and stacking faults.